2017
DOI: 10.1038/mi.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL mediates RIPK3-dependent necrosis in M. tuberculosis-infected macrophages

Abstract: Virulent Mycobacterium tuberculosis (Mtb) triggers necrosis in host Mφ, which is essential for successful pathogenesis. Here we demonstrate that necrosis of Mtb-infected Mφ is dependent on the action of the cytosolic kinase Receptor Interacting Protein 3 (RIPK3) and the mitochondrial Bcl-2 family member protein B-cell lymphoma - extra large (Bcl-xL). RIPK3-deficient Mφ are able to better control bacterial growth in vitro and in vivo. Cytosolic RIPK3 translocates to the mitochondria where it promotes necrosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
78
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 71 publications
13
78
2
3
Order By: Relevance
“…These experiments conclusively demonstrated that TNT triggers necroptosis, a form of programmed cell death with molecular features similar to necrosis, preventing viruses from replication in infected cells (Dondelinger et al, 2016; Weinlich et al, 2017). These findings are consistent with recent results published by Zhao et al (2017), who showed that cell death of macrophages infected with virulent Mtb is dependent on RIPK3 and MLKL and that Ripk3 −/− mice were more resistant to Mtb infection than WT mice. Our study established that TNT is the main necroptosis-inducing factor in macrophages infected with Mtb.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These experiments conclusively demonstrated that TNT triggers necroptosis, a form of programmed cell death with molecular features similar to necrosis, preventing viruses from replication in infected cells (Dondelinger et al, 2016; Weinlich et al, 2017). These findings are consistent with recent results published by Zhao et al (2017), who showed that cell death of macrophages infected with virulent Mtb is dependent on RIPK3 and MLKL and that Ripk3 −/− mice were more resistant to Mtb infection than WT mice. Our study established that TNT is the main necroptosis-inducing factor in macrophages infected with Mtb.…”
Section: Discussionsupporting
confidence: 93%
“…TNF-α-dependent cell death of macrophages is associated with apoptosis (Riendeau and Kornfeld, 2003) and was observed with avirulent Mtb strains and/or low bacillary loads (Lee et al, 2006). Our observation that virulent Mtb bypasses the TNF-α receptor and RIPK1 activation and directly activates RIPK3 is consistent with previous studies (Riendeau and Kornfeld, 2003; Zhao et al, 2017). Roca and Ramakrishnan (2013) showed in zebrafish that Mycobacterium marinum induces RIPK1/RIPK3-dependent necroptosis in the presence of excess TNF-α.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations